Deep convolutional neural network designed for age assessment based on orthopantomography data - Kahaki S.M.M.; Nordin M.J.; Ahmad N.S.; Arzoky M.; Ismail W. (Springer London, 2024)
Indexed by WOS/Scopus/ERA